Ability and Preparedness of Family Physicians to Recognise and Treat Adolescent Mental Health Disorders in Nigeria and Ghana - Tijani Idris Ahmad Oseni; Magdalene Mensah-Bonsu; Fatima Mohammed Damagun; Tawakalit Olubukola Salam; Kumbert John Sonny; Edwina Beryl Addo Opare-Lokko; Eve Namisango; Onyenwe Chibuike Ephraim (SAGE Publishing, 2023)
Background: Management of mental health disorders has not been fully integrated into primary care despite been advocated by the World Health Organisation (WHO) and the World Organisation of Family Doctors (WONCA). This study therefore seeks to assess the ability and preparedness of Family Physicians to recognise and treat mental health disorders in adolescents. Methodology: A descriptive cross-sectional study of 233 randomly selected Physicians Practicing in Family Medicine Clinics in Nigeria and Ghana was conducted using a semi structured self-administered questionnaire that was developed by the researchers and validated with a Cronbach's alpha coefficient of .85. Data analysis was done with the Statistical Package for Social Sciences™ (IBM Corp, Armonk, NY, USA) version 22.0. Results: Respondents had a mean age of 43 ± 8 years, were mostly males 130 (55.79%), practised in Nigeria 168 (72.10%) and have been in practice for over 10 years 149 (63.95%). Majority of respondents 153 (65.67%) received at least one Medical Education sessions in mental health in the preceding 12 months of the study. Out of these, 146 (95.42%) said the sessions enhanced their knowledge of mental health, and 121 (79.08%) said the sessions enhanced their abilities and preparedness to attend to patients with mental disorders. Barriers included stigmatisation 156 (66.95%), poor facilities 136 (58.37%), non-conducive environment 135 (57.94%) and non-cooperation from patients 133 (57.08%). Conclusion: This study showed that a lot of family physicians in Ghana and Nigeria are able and prepared to manage adolescent mental health disorders. They however cited stigmatisation, poor facilities and non-conducive environment as barriers to management of adolescent mental health disorders in primary care. Considering the severity of the disorder, there is a need to increase the training of Family Physicians in the management of adolescent mental health.